Coconut Mesocarp Extracts to Control Fusarium musae, the Causal Agent of Banana Fruit and Crown Rot - Jesús Aidmir Yeikame Morelia-Jiménez; Beatriz Montaño-Leyva; Francisco Javier Blancas-Benitez; Luz del Carmen Romero-Islas; Porfirio Gutierrez-Martinez; Luis Guillermo Hernandez-Montiel; Pedro Ulises Bautista-Rosales; Ramsés Ramón González-Estrada (AgriEngineering, 2023)
Crown rot, caused by Fusarium species, is the most devastating postharvest disease in bananas. Fungicides are traditionally applied as a postharvest treatment to control crown rot in bananas. However, there is a need to research environmentally friendly compounds as postharvest treatments instead of chemical fungicides. The phenolic compounds gallic acid, protocatechuic acid, and chlorogenic acid were identified in coconut mesocarp extract. Overall, the treatments were more efficient in crown-based than fruit-based culture mediums. The mycelial development was inhibited in a range from 20 to 26% (applying coconut mesocarp extract at 5%) compared to the control. Sporulation and spore germination were significantly inhibited, with a reduction of 88% in spore production and 91% in spore germination inhibition compared to the control. In in vivo tests, the aqueous extracts were effective by limiting the percentage of infected fruit, crown rot, and fruit severity. The use of coconut mesocarp extracts can be an effective and environmentally friendly alternative to the use of fungicides for controlling Fusarium musae on bananas.